Effectiveness of The Education Level, Understanding of Accounting and Work Experience on the Quality of Financial Statements in The MSMEs Indonesian Local Government - Julita, Era; Dura, Justita (JURNAL AKUNTANSI DAN BISNIS : Jurnal Program Studi Akuntansi, 2024)
Micro, Small and Medium Enterprises (MSMEs) face several obstacles so that in their business it is difficult to develop, one of which lies in financial management in their business activities so that the presentation of financial statements poses its own problems for MSMEs. The purpose of this study is to determine the influence of education level, accounting understanding and work experience on the quality of financial statements produced by MSMEs in MaLang City. This research approach uses quantitative techniques and measures the results using the Likert scale sourced from questionnaire data. Using agency theory and stewardship theory. The sampling technique uses a purposive sampling method with predetermined criteria. The population of this study is MSMEs in Malang City, the number of respondents who filled out questionnaires that have been distributed through whatsapp grub assisted by the MSME cooperative office in Malang City 45 respondents but who met the criteria of 38 respondents. Using analysis techniques which include validity, reliability and hypothetical tests used are R tests and T tests with the help of SPSS 25 software. The results showed that 53.4% of the influence of the quality of MSME financial statements was influenced by the variables studied. Understanding accounting has a significant positive effect on the quality of financial statements, the level of education and work experience does not affect the quality of financial statements.